The In Situ Observation of Phase Transformations During Intercritical Annealing of a Medium Manganese Advanced High Strength Steel by High Energy X-Ray Diffraction - Hu, Xiaohua; Mueller, Josh J.; Sun, Xin; De Moor, Emmanuel; Speer, John G.; Matlock, David K.; Ren, Yang (Frontiers in Materials, 2021)
The mechanical performance of inter-critically annealed medium Mn steels is dependent on the stability of the retained austenite relies on the C and Mn content in it. The inter-critical annealing is one of the two heat-treatment approaches which can increase the C and Mn content and make the austenite more stable. Understanding solute partitioning kinetics that occur during inter-critical annealing is critical to predict mechanical properties of such materials. In the current work, in-situ high energy X ray diffraction (HEXRD) with the use of a Linkam1500 heating stage were conducted for gaining understanding the microstructure evolution during the inter-critical annealing of a Fe 0.19C 4.39Mn steel from an as quenched condition. The ThermoCalc equilibrium calculation is used here for gaining better insights and understanding. For the first time, the initial austenite dissolution followed by Cementite precipitation is observed and the austenite fraction can reach as high as 20% after 30 minutes of holding at 650oC and cooled done to room temperature, although still considerably lower than the equilibrium austenite fraction. The lattice strain of the austenite also increases, indicating increasing C and Mn content in it which is beneficial for the transformation induced plasticity during deformation.